2011
DOI: 10.3109/00952990.2011.600387
|View full text |Cite
|
Sign up to set email alerts
|

Parental Prescription Opioid Abuse and the Impact on Children

Abstract: By assessing these parental characteristics, clinicians may be able to assess children who are at risk for impairment and, in turn, may be in need of mental health services. Due to limitations of this study, further evaluation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In the present study, we analyzed the alcohol drinking habits [15] of outpatient clinic in our hospital. Initial idea comes from our impression that alcohol drinkers well tolerate from side effect of pregabalin or tramadol/acetaminophen.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we analyzed the alcohol drinking habits [15] of outpatient clinic in our hospital. Initial idea comes from our impression that alcohol drinkers well tolerate from side effect of pregabalin or tramadol/acetaminophen.…”
Section: Discussionmentioning
confidence: 99%
“…However, to maintain anonymity, users’ names will not be presented, and all quotes will be paraphrased having been checked in Mumsnet and Google that they cannot be used to identify the thread. Evidence on a specific link between parenting and misuse of medicines is scant, but groups such as pregnant and parenting women have been considered particularly concerning in relation to opioid misuse [25] and effects on children [26].…”
Section: Methodsmentioning
confidence: 99%
“…Many of the studies employing a cross-sectional methodology found some evidence of an association between parental offending and child mental health outcomes. In a convenience sample of 14 opioid dependent parents and their 24 children, Ashrafioun, Dambra, and Blondell (2011) found that the children of parents with a self-reported history of arrest or current court involvement were significantly more likely to have an unmet need for mental health services. No additional analyses were conducted to determine if this finding could be explained by other factors.…”
Section: Parental Offending and Child Mental Health Problemsmentioning
confidence: 99%